Pseudocybaeota (Araneae: Cybaeidae): a new spider genus endemic to coastal Pacific Northwestern United States of America - Bennett, Robb; Copley, Claudia; Copley, Darren (Zootaxa, 2022)
The forested habitats of the west coast of North America are home to a diverse array of endemic Cybaeinae spider taxa (Araneae: RTA clade: Cybaeidae). Most of those taxa have very restricted distributions within an area of the western United States of America from the Olympic Peninsula of northwestern Washington to the northern half of the Californian Floristic Province of California, a well-known biodiversity hotspot. Here we describe Pseudocybaeota Bennett gen. nov. with type species Cybaeus perditus Chamberlin & Ivie (= Pseudocybaeota perdita (Chamberlin & Ivie) comb. nov.) and including two new species, P. butterfieldi Bennett spec. nov. and P. tuberculata Bennett spec. nov. These rarely collected species are restricted to forested habitats in small areas of the coastal watersheds of the Olympic Peninsula (P. perdita comb. nov.), southern Curry and adjacent northern Del Norte Counties in Oregon and California, respectively (P. tuberculata spec. nov.), and Humboldt County in northwestern California (P. butterfieldi spec. nov.). In addition to descriptions of the genus and both sexes of its included species we provide diagnoses, illustrations, an identification key, and distribution maps for the species of this distinctive new genus.